2013
DOI: 10.1681/asn.2013030243
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-2 Inhibitors

Abstract: The critical contribution of aquaporin-2 (AQP) to water homeostasis in mammals is highlighted by the severe concentrating defects seen in humans with mutations in the AQP2 gene and in mice that are AQP2 null or have loss-of-function mutations in AQP2. 1,2 The role of the antidiuretic hormone vasopressin and its receptor, V2R, in the signaling cascade that leads to membrane accumulation of AQP2 in collecting-duct principal cells, and to an increase in renal water reabsorption, is well established. 3 The involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Sin embargo, en los pacientes que reciben tratamiento prolongado con sales de litio (por ejemplo para el tratamiento de desórdenes bipolares) se han observado alteraciones en la regulación de la acuaporina-2, el canal epitelial de sodio y los transportadores de urea (UT-A1 y UT-B), con lesión y pérdida de las células principales del túbulo colector de la nefrona, lo cual puede producir una lesión irreversible del mecanismo de concentración urinaria 21,22 . Por otro lado, en los pacientes que reciben tratamientos cortos con sales de litio se puede observar recuperación completa de la alteración tubular renal 23 .…”
Section: Diabetes Insípida Nefrogénica Secundariaunclassified
“…Sin embargo, en los pacientes que reciben tratamiento prolongado con sales de litio (por ejemplo para el tratamiento de desórdenes bipolares) se han observado alteraciones en la regulación de la acuaporina-2, el canal epitelial de sodio y los transportadores de urea (UT-A1 y UT-B), con lesión y pérdida de las células principales del túbulo colector de la nefrona, lo cual puede producir una lesión irreversible del mecanismo de concentración urinaria 21,22 . Por otro lado, en los pacientes que reciben tratamientos cortos con sales de litio se puede observar recuperación completa de la alteración tubular renal 23 .…”
Section: Diabetes Insípida Nefrogénica Secundariaunclassified
“…There are compelling possibilities in the quest for AQPbased treatment, yet little progress has been made so far. A few reported inhibitors of AQP are appropriate for clinical trials, none of them showed any specificity for AQP3 (Niemietz and Tyerman, 2002;Migliati et al, 2009;Brown and Lu, 2013). AQP1, a close congener of AQP3 in terms of protein sequence, reported to be inhibited by tetraethylammonium salts (Brooks et al, 2000), acetazolamide (Bing et al, 2004), bumetanide (Kourghi et al, 2016), and DMSO (Vanhoek and Vanos, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…There are compelling opportunities, yet so far little progress, in the search for AQP-based therapeutics. There are a few reported AQP inhibitors suitable for clinical trials; however, none of them has shown any specificity for AQP3 [19][20][21]. AQP1, a close congener of AQP3 in terms of protein sequence, reported to be inhibited by tetraethylammonium salts [22], acetazolamide [23], bumetanide [24], and DMSO [25].…”
Section: Introductionmentioning
confidence: 99%